Disclosing Information and Creative Work Practices to MSMEs in Semarang City - Amboningtyas, Dheasey; Lestari, Sinta Petri; Haryono, Andi Tri (Economic Education Analysis Journal, 2024)
This study aims to investigate how MSMEs in Semarang City use social media to enhance knowledge exchange, foster creative work practices, and achieve sales success. The way knowledge exchange is perceived within firms is gradually shifting due to the proliferation of social media platforms, most of which allow employees to collaborate on projects, share ideas, and obtain information. In Semarang City, MSMEs are no different. By utilizing social media, they can also promote innovative work practices. Social media provides an outlet for knowledge and idea sharing. Aside from that, appropriate social media use can foster a creative culture. Examining the connections between MSMEs in Semarang City's usage of social media, information sharing, creative work practices, and sales success is the goal of this study. PRISMA and bibliometric analysis make up the research approach. The research's findings indicate that over twenty publications, particularly in relation to MSMEs which are rapidly expanding in Semarang City state that social media is a useful platform for exchanging ideas and information. The findings of the study indicate that a number of other factors contribute to the smooth operation of everything in addition to social media. Like working together and cooperatively among staff members to enhance client.